Poverty as the Explicit Theme in Aravind Adiga’s Between the Assassinations - Nidhi Gupta (The Creative Launcher, 2021)
Adiga is an influential voice of 21st century India. He depicts the agony of the subjugated class of India. In Between the Assassinations, Adiga presents a vivid picture of lives of the marginalized. The novel contains the theme of poverty, hunger and exploitation of poor as the main theme. The novel is a scrupulous examination of microcosm of India. It is a simmering fury at the wide gulf between the haves and have not’s. The novel provides a glimpse of the India of Darkness through its twelve stories spinning around the assorted aspects of life in the town Kittur. The novel highlights the social and political turmoil of India during 1984 and 1991 and reflects how poverty, the mother evil, gives rise to other evils in the society. The novel contains a wide array of characters from famished person to the richest person of the town, Kittur. It describes the harsh realities of poor villagers who have to but migrate to cities in order to survive and live on the streets.